Implementation of School Principal Entrepreneurship Leadership in the Covid-19 Pandemic Era at Karitas Catholic High School in Tomohon City - Pontoh, Bernadette E.; Tambingon, Henny N.; Lengkong, Jeffry S.J.; Rotty, Viktory Nicodemus Joufree (Asia Pacific Journal of Management and Education (APJME), 2021)
The purpose of this study is to describe the implementation of entrepreneurial leadership during the Covid-19 pandemic at Karitas Catholic High School in Tomohon City, the supporting and inhibiting factors as well as the solutions for handling them. This research used a descriptive qualitative approach. The research subjects were five people consisting of a school principal and four vice principals. The data were collected from interviews, observation, and documentation studies. The data were analyzed by an interactive model. The findings indicate that entrepreneurial leadership was implemented through the principal role as an explorer, a miner, an accelerator, and an integrator. The supporting factors are teachers’ IT skills, government allowances, parents’ support and proactivity, online learning facilities, and entrepreneurial instincts of teachers and students. The inhibiting factors are the late payment of tuition fees, the uncertainty of parents' income, the late disbursement of the government's school operational assistance (BOS) funds and the foundation's compulsory funds, the complexity of the foundation's centralized system, and the lack of online learning facilities. The efforts to overcome the inhibiting factors are coordination with parents, overcoming arrears, recording the number of students without online learning facilities, and conducting offline learning for them. The results suggest continuing to implement entrepreneurial leadership more openly and creatively, increase the supporting factors, and minimize the inhibiting factors with various efforts.